Low frequency of broadly neutralizing HIV antibodies during chronic infection even in quaternary epitope targeting antibodies containing large numbers of somatic mutations. (February 2016) - Hicar, Mark D.; Chen, Xuemin; Kalams, Spyros A.; Sojar, Hakimuddin; Landucci, Gary; Forthal, Donald N.; Spearman, Paul; Crowe, James E.
Highlights: We isolated a large panel of human mAbs to HIV that were identified by binding to VLPs. Many of these mAbs possess large numbers of somatic mutations and recognized quaternary (Qt) epitopes. Surprisingly, most highly mutated QtAbs did not exhibit a high level of neutralizing activity. Abstract: Neutralizing antibodies (Abs) are thought to be a critical component of an appropriate HIV vaccine response. It has been proposed that Abs recognizing conformationally dependent quaternary epitopes on the HIV envelope (Env) trimer may be necessary to neutralize diverse HIV strains. A number of recently described broadly neutralizing monoclonal Abs (mAbs) recognize complex and quaternary epitopes. Generally, many such Abs exhibit extensive numbers of somatic mutations and unique structural characteristics. We sought to characterize the native antibody (Ab) response against circulating HIV focusing on such conformational responses, without a prior selection based on neutralization. Using a capture system based on VLPs incorporating cleaved envelope protein, we identified a selection of B cells that produce quaternary epitope targeting Abs (QtAbs). Similar to a number of broadly neutralizing Abs, the Ab genes encoding these QtAbs showed extensive numbers of somatic mutations. However, when expressed as recombinant molecules, these Abs failed to neutralize virus or mediate ADCVI activity. Molecular analysis showed unusually high numbers of mutations in the Ab heavy chain framework 3 region of the variable genes. The analysis suggests that large numbers of somatic mutations occur in Ab genes encoding HIV Abs in chronically infected individuals in a non-directed, stochastic, manner.